MOLECULAR IDENTIFICATION OF NOVEL PROBIOTIC BACTERIA ISOLATED FROM COW MILK AND ITS ANTIBACTERIAL APPLICATIONS - BABINA CHANU KHOMDRAM*; A.THIRUMANI DEVI (The Journal of Research ANGRAU, 2024)
The purpose of the study conducted in the year 2021 was to isolate and identify Lactobacillus species through biochemical characterization and to find antibacterial potential of the species. Researchers collected milk sample from local milk vendor, Eachanari in December, 2021. In an Enriching MRS broth the colonies were isolated and loop full of isolate were streaked on MRS agar plate. By morphological characteristics determined through gram staining method the isolated bacteria were identified as Lactobacillus species. Through different identification methods such as casein digestion, acid and salt tolerance the isolate was characterized for probiotic properties. In a skim milk agar plate the isolated strain digested casein. This indicated production of protease enzyme which is a significant probiotic property. In MRS broth, an acid tolerance test was conducted at pH levels 3, 4, 5, 6, 7 and 8. The isolate was able to endure both an extremely acidic pH and alkaline media. NaCl tolerance test was done in MRS broth at concentrations of 3%, 4%, 5%, 6%, 7%, and 8% NaCl. The isolate survived well in solutions containing 3%, 4%, and 6% NaCl. After biochemical studies, molecular identification was carried out to identify the probiotic starin. The isolated probiotic was identified as Limosilactobacillus fermentum strain BTFSN. The isolated strain was then checked for antibacterial activity against three pathogens. Zone of inhibition were observed. The study indicated that Lactobacillus species from milk sample have potential probiotic properties and possess antimicrobial property.